KOMUNIKASI INSTRUKSIONAL DALAM PENDIDIKAN PEMBENTUKAN (DIKTUK) BINTARA POLRI DI SEKOLAH POLISI NEGARA POLDA RIAU - Hidayati, Herlenny; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Pendidikan Pembentukan (Diktuk) Bintara Polri is an education to form and equip students to become members of the Police who have the knowledge, skills, abilities, resilience, attitudes and commendable behavior in order to carry out Police duties. The success achieved by the graduates of Bintara Polri and the position of the Police Force Police who are in the midst of the people who need the services and assistance from the police will almost certainly deal with police officers with the rank of Bintara, this shows that their education has great success and influence on their service they. So in the process of learning in Pendidikan Pembentukan (Diktuk) Bintara Police in Police School Police Riau educators use instructional communication. The purpose of this research is to know the instructional communication method used by educator in learning process of Pendidikan Pembentukan (Diktuk), instructional media used by educator in learning process of Pendidikan Pembentuksn (Diktuk), and communication barrier that happened in teaching and learning process in Pendidikan Pembentukan (Diktuk) Bintara Police at Sekolah Polisi Polda Riau.This research uses qualitative research methods with the presentation of descriptive analysis. Informant of this research is Educator (educators and instructor) and student of Polri Bintara which is chosen purposively. Data collection techniques used were interviews, observation and documentation. Data validity technique used in this research is extension of participation and triangulation.The results obtained showed that instructional methods used by educators in teaching and learning process are lecture method, Q & A method, demonstration method and simulation method. Instructional media used by educators in the delivery of learning is visual media and media props. Barriers to instructional and student instructional communication in the learning process include cultural barriers and barriers to communicants. In cultural barriers, researchers encounter obstacles to differences in norms and regulations adopted previously by students with those applied in Pendidikan Pembentukan (Police) so that students become overwhelmed in self-adjustment. On the barriers to the communicant there are physical barriers students Bintara Police with activities and solid learning to make students quickly tired and sleepy.Keyword : Instructional Communication, Pendidikan Pembentukan (Diktuk) Bintara Polri